RESISTENSI ATAS PENGENDALIAN TEMBAKAU TERHADAP HAK-HAK EKONOMI, SOSIAL, DAN BUDAYA DI KALANGAN PETANI SRINTHIL - Khanifa, Nurma Khusna (Kopertais Wilayah X Jawa Tengah, 2018)
AbstractThe World Health Organization (WHO) has indeed adopted the Framework Convention on Tobacco Control (FCTC) in the 56th World Health Assembly in 2003. The FCTC provides reference to the importance of worldwide tobacco control. The impact of this resistance is the tobacco farmers of Temanggung Regency. Tobacco planted on the slopes of Sindoro and Sumbing mountains, Temanggung Regency, is the number one tobacco producer of tobacco srinthil. Srinthil Tobacco has been listed as Geographical Indication No. ID G 000 000 027 at the Directorate General of Intellectual Property. Srinthil is located in the village of Legokari Tlogomulyo District has a high quality has placed it as a green gold title. Cultural heritage has left the custom of ritual in obtaining the quality of tobacco. But behind the success of tobacco as one of the commodities that have a large contribution to state revenues, the government actually issued several policies against the development of marketing. The government’s appreciation of the tobacco leaf lately seems half-hearted. For farmers, tobacco is not just a commodity. Tobacco is an important part of the spiritual life. Elements of tobacco in the form of chopping, clove or cigarettes in offerings that symbolize fire, water, air and soil. Thus tobacco is considered as a balance between man and nature. The way to see the tobacco issue from a health standpoint by negating this other perspective is not only inappropriate but rather misleading. The reason is that tobacco is a legal and superior commodity that has a vital role with the linkage of economic, social and cultural interests. Therefore, the government can not yet accommodate the human rights of economic, social and cultural rights.AbstrakWorld Health Organization (WHO) memang telah mengadopsi Framework Convention on Tobacco Control (FCTC) dalam Sidang Kesehatan Dunia (World Health Assembly) ke-56 pada 2003. FCTC ini memberikan rujukan tentang betapa pentingnya pengendalian tembakau di seluruh dunia. Dampak yang dirasakan adanya resistensi ini ialah petani tembakau Kabupaten Temanggung. Tembakau yang ditanam di lereng gunung Sindoro dan Sumbing, Kabupaten Temanggung, sebagian adalah penghasil tembakau kualitas nomor satu, yakni tembakau srinthil. Tembakau Srinthil telah terdaftar sebagai Indikasi Geografis No. ID G 000 000 027 di Direktorat Jenderal Kekayaan Intelektual. Srinthil berada di Desa Legoksari Kecamatan Tlogomulyo ini memiliki berkualitas tinggi telah menempatkannya sebagai sebutan emas hijau. Warisan budaya telah meninggalkan adat berupa ritual dalam mendapatkan mutu tembakau. Tetapi dibalik kesuksesan tembakau sebagai salah satu komoditas yang memiliki sumbangsih besar terhadap penerimaan negara, pemerintah justru mengeluarkan beberapa kebijakan yang menentang terhadap perkembangan pemasaran. Apresiasi pemerintah terhadap daun tembakau belakangan nampak setengah hati. Bagi para petani, tembakau memang tak sekedar komoditi. Tembakau menjadi bagian penting dari kehidupan spiritual. Unsur tembakau berupa rajang, kretek atau rokok dalam sesaji yang melambangkan api, air, udara dan tanahal. Dengan demikian tembakau dianggap sebagai penyeimbang antara manusia dan alam. Cara melihat persoalan tembakau dari sudut pandang kesehatan dengan meniadakan perspektif lainnya ini bukan hanya tidak tepat melainkan justru menyesatkan. Alasannya, tembakau adalah barang legal dan komoditi unggulan yang mempunyai peran vital dengan pertautan kepentingan ekonomi, sosial dan budaya. Oleh sebab itu pemerintah belum bisa menjadi mengakomodir hak-hak manusia (human rights) hak-hak ekonomi, sosial dan budaya.